1999
DOI: 10.1103/physreva.60.2873
|View full text |Cite
|
Sign up to set email alerts
|

Associative detachment, dissociative attachment, and vibrational excitation of HCl by low-energy electrons

Abstract: An improved nonlocal resonance model for electron-HCl collisions is con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 36 publications
(59 reference statements)
1
32
0
Order By: Relevance
“…The model ofČížek et al agreed with experiment better even though they fully adopted the short-range part of the nonlocal resonance model of Domcke and Mündel [20]. Better agreement was obtained both for the shape of the DA bands and for the VE functions [21]. Additionally, the model ofČížek et al predicted features in the AD spectra that were confirmed by the experiment [11] and even very fine details (outer well resonances and boomerang structures) in the VE spectra.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The model ofČížek et al agreed with experiment better even though they fully adopted the short-range part of the nonlocal resonance model of Domcke and Mündel [20]. Better agreement was obtained both for the shape of the DA bands and for the VE functions [21]. Additionally, the model ofČížek et al predicted features in the AD spectra that were confirmed by the experiment [11] and even very fine details (outer well resonances and boomerang structures) in the VE spectra.…”
Section: Introductionmentioning
confidence: 79%
“…It described qualitatively all the features observed in various cross sections. This model has been improved byČížek et al [21] by adding the dependence of the dipole-modified threshold exponent on the internuclear distance and determining the long-range part of the HCl − potential-energy function from accurate ab initio calculations. The model ofČížek et al agreed with experiment better even though they fully adopted the short-range part of the nonlocal resonance model of Domcke and Mündel [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the local theory for DEA fails in the case of a broad shape resonance with a typical example of low-energy DEA to the H 2 molecule [10,12] driven by a very broad 2 u resonance. A similar situation is observed in the case of hydrogen halides [13][14][15] where, in addition to the effect of the broad resonance, the long-range dipolar interaction strongly affects the DEA dynamics which cannot be described by the local theory. On the other hand, in the case of a relatively narrow resonance at not very low energies and in the absence of a strong long-range interaction, the local theory was demonstrated to be very successful.…”
Section: Introductionmentioning
confidence: 77%
“…Application of this method leads to the FC transition point R v defined by Eq. (13). Although the FC point is complex, we will neglect again its imaginary part that introduces a small error for narrow resonances.…”
Section: Nonlocal Theory: Comparison With Fmentioning
confidence: 99%